The Production of Interdental Fricatives by English as a Foreign Language Students in English Course Bandung - Salwa Fadila Firdaus; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Linguistics and ELT Journal, 2020)
Every language has its characteristics in the production of sound. When learning a new language, one probably encountered unfamiliar sounds. For EFL students in Indonesia, they will find it hard to pronounce interdental fricative sound like [θ] and [ð] because, in Indonesian pronunciation, there are no interdental fricative sounds. Therefore, the limited consonant sounds in Indonesian that is not similar become one of the barriers for the students to pronounce the words in English properly. For instance, the words that contain interdental fricative sounds in word-initial position as in 'this' and 'thin', medial as in ‘father’ and ‘authority’, and final part as in ‘booth’ and ‘truth’. Based on this problem, this research attempts to find out and analyze the production of voiceless and voiced interdental fricatives by EFL students in Bandung using the help of software Praat (Boersma, 2001). The data were collected from four students with their voice recordings in pronouncing the words in English that contain an initial, medial and final position of interdental fricative. The result shows that the voiceless interdental fricative [θ] is produced as [d],[t],[th] and elimination of [θ] sound, while the voiced interdental fricative sound [ð] is produced as [d], [t] sounds.